Dispersion of nanodiamond particles
Patent Information
- Application Number
- JP2022508951
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-13
- Filing Date
- 2020-08-13
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2040-08-13
Smart Images

Figure 0007644935000007 
Figure 0007644935000008 
Figure 0007644935000009
Abstract
Description
[Technical field]
[0001] This application describes methods for discontinuing nanodiamond aggregates and compositions produced using these methods. [Background technology]
[0002] Nanodiamonds have a number of useful properties, ranging from lubrication to nanofillers for polymer and metal composites, as well as medical applications. Nanodiamonds produced by the detonation process are biocompatible, inexpensive to produce, and scalable. In recent years, advances in the preparation of aqueous dispersions of nanodiamonds have facilitated their use in biomedical applications and polymer composites.
[0003] Many existing and potential applications, especially in the biomedical and pharmaceutical fields, rely on nanodiamonds with a very small average particle size. For example, nanoparticles with particle sizes falling in the range of 10-100 nanometers can be suspended and circulated in the blood and are easily removed from the bloodstream by the kidneys. Nanoparticles smaller than 10 nanometers have several additional properties that are highly desirable in biomedical applications, such as the ability to pass through the blood-brain barrier or the nuclear pore complex of cells.
[0004] Unfortunately, nanodiamonds have a strong tendency to aggregate, forming tightly bound aggregates containing 10, 20, or even 100 or more primary nanodiamond particles. Detonation nanodiamond particles in particular are known to form aggregates that cannot be broken down by conventional means such as sonication or grinding. It is therefore highly desirable to develop methods to break up nanodiamond aggregates and obtain single-digit nanodiamonds (i.e., single-digit nanodiamonds having a diameter of less than 10 nanometers).
[0005] Several dispersal methods for suspending nanodiamonds are known in the art, including ball milling, attrition grinding, and bead-assisted sonication (BASD). Each of these techniques can be used to obtain single-digit nanodiamond suspensions. Unfortunately, each of the known dispersal techniques has one or more significant drawbacks. For example, many known dispersal techniques incorporate impurities into the nanodiamond material, which is a significant concern in the biomedical context. In addition, many known dispersal methods are complex, require expensive custom equipment, and / or significantly increase the cost of obtaining single-digit nanodiamonds.
[0006] Recently, US Patent Application Publication No. 2015 / 0038593, incorporated herein by reference, disclosed a dry media attrition milling process that utilizes crystalline grinding media such as sodium chloride or sucrose to break up nanodiamond aggregates. This process provided several important improvements over previously known wet milling processes that required the use of zirconia as a grinding media.
[0007] Unfortunately, the process disclosed in Publication '593 still exhibits several difficulties that limit its usefulness in preparing discrete nanodiamonds for biomedical applications. In addition to being relatively expensive and expensive to maintain, the attrition mill uses steel jars, shafts and balls, which represent a source of metal contaminants and are subject to severe wear and corrosion during the milling process, especially in the presence of salts. As a result, nanodiamonds produced using the process described in Publication '593 are often contaminated with metal impurities, including iron and other steel constituents. Although many of the metal impurities are soluble in acid, they require the use of additional purification steps that reduce the overall efficiency and increase the cost and complexity of the process. In addition, although the process described in Publication '593 can reduce the size of nanodiamond aggregates to an average diameter of 30-50 nanometers, single-digit nanodiamonds cannot be obtained unless the dispersion pH is adjusted to approximately 11 at the completion of milling. This requires the introduction of additional process steps, further increasing the cost and complexity. US Patent Application Publication No. 2018 / 0134563, the entire disclosure of which is expressly incorporated herein by reference, discloses the use of ultrasound to disrupt nanodiamond aggregates in aqueous sodium chloride slurries to disintegrate nanodiamond aggregates. This salt-assisted ultrasonic disintegration (SAUD) technique can disintegrate detonation nanodiamond (DND) aggregates into single-digit particles by ultrasonic cavitation in supersaturated salt suspensions, eliminating the need for both expensive grinders and ceramic microbeads. Summary of the Invention
[0008] Aspects of the present invention relate to various methods of discretizing nanodiamond aggregates. In some embodiments, the method includes (a) mixing the aggregated nanodiamond aggregates in a liquid medium containing a solvent with ozone oxidized nanodiamond aggregates, where the aggregates and the solvent are in a slurry having a pH of about 8 to about 11, for example about 9 to about 10, and (b) sonicating the mixture for a sufficient time to generate nanodiamond particles having a median particle size smaller than the median particle size of the aggregated nanodiamond aggregates.
[0009] In another aspect, the present invention relates to nanodiamond particles prepared using the methods described herein. A further aspect relates to compositions comprising said nanodiamond particles.
[0010] Other objects and features will be in part apparent and in part pointed out hereinafter. [Brief description of the drawings]
[0011] [Figure 1] Dissociation of DND-O3 and DND-O2 by horn sonication. (i) Adjustment of pH to 9.5 followed by horn sonication for 280 min. (ii) Ultracentrifugation at 12000 rpm for 10 min. (1) DND-O3, (2) S-DND-O3, (3) P-DND-O3. [Diagram 2] XRD pattern of DND surface graphitized at 950 °C for 5 h under argon atmosphere, showing the (111), (220), and (311) peaks of the diamond structure. [Diagram 3] FTIR of (1) as-received DND, (2) graphitized DND, (3) DND-O3, and (4) DND-O2. [Figure 4]a) Z-average diameter of diluted DND-O3 aqueous slurry during horn sonication. b) Z-average diameter of diluted (1) DND-O3 and (2) DND-O2 after centrifugation at 4500 rpm for 5 min during horn sonication. c) Photograph of (1) DND-O3 and (2) DND-O2 slurries when the centrifuge tubes are inverted after 280 min of horn sonication. d) Particle size distribution of (1) S-DND-O3 and (2) S-DND-O2. [Diagram 5] Redispersibility of dry DND powder (0.02 wt%) in water without additional treatment: (1) S-DND-O3, (2) S-DND-O2. [Figure 6] Particle size distribution and photograph of S-DND-O3 slurry redispersed from dry powder. [Figure 7] a) FTIR of (1) DND-O3, (2) S-DND-O3 and (3) P-DND-O3. b) Raman spectra of (1) DND-O3, (2) S-DND-O3 and (3) P-DND-O3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Methods for disaggregating (deagglomerating) nanodiamond aggregates are provided herein. Various methods for disaggregating nanodiamond aggregates include (a) mixing aggregated nanodiamond aggregates in a liquid medium including a solvent (e.g., water) with ozone oxidized nanodiamond aggregates, where the aggregates and the solvent are in a slurry having a pH of about 8 to about 11, e.g., about 9 to about 10, and (b) sonicating the mixture for a sufficient time to generate nanodiamond particles having a median particle size smaller than the median particle size of the aggregated nanodiamond aggregates.
[0013] Various methods include disintegrating ozone-oxidized nanodiamond aggregates in alkaline water by horn sonication. The methods described herein are useful for producing compositions containing nanodiamonds, for example, having an average particle size of less than 10 nanometers in diameter.
[0014] The method described herein may provide several advantages over previously known nanodiamond separation methods. For example, the method does not incorporate any contaminants that are impossible or difficult to remove into the resulting nanodiamonds - an important advantage in applications requiring high purity nanodiamonds, especially biomedical applications. The process described herein does not require high-cost materials or expensive equipment, such as zirconia microbeads or attrition mills, and can be carried out by virtually any laboratory or mass-produced, for example by employing continuous-flow sonication cells, for large-scale production. In addition, the nanodiamonds produced using the process described herein can be dried and then redispersed to form a colloidal dispersion of nanodiamonds that retains a relatively small particle size, which represents another advantage over previously known separation techniques.
[0015] As used herein, the terms "nanodiamond aggregate", "aggregated nanodiamond" and "aggregated nanodiamond assembly" each refer to a nanodiamond aggregate comprising multiples of primary nanodiamond particles, for example, a nanodiamond aggregate comprising at least 10, 20, 30, 40, 50, 100 or 1000 or more primary nanodiamond particles.
[0016] As used herein, the term "disintegrating" refers to breaking down the aggregates into smaller aggregates (i.e. containing fewer primary particles) that are and contain individual primary nanodiamond particles.
[0017] As used herein, the term "particle size" is defined as the diameter of the smallest circular hole through which a particle (including agglomerates of particles) can pass freely. For example, the particle size of a spherical agglomerate is equivalent to the diameter of the agglomerate, while the particle shape of an ellipsoidal agglomerate corresponds to the length of its longest minor axis.
[0018] As described above, the ultrasonic treatment may be performed for a time sufficient to reduce the median particle size of the nanodiamonds to within the desired range. The suitable frequency, intensity and duration of the ultrasonic treatment will depend on the desired nanodiamond particle size and the particular equipment used. For example, the duration of the ultrasonic treatment may range from about 5 minutes to about 500 minutes. The ultrasonic treatment may be performed for at least about 5 minutes, about 10 minutes, about 15 minutes, about 20 minutes, about 30 minutes or about 60 minutes. Exemplary ranges include about 5 minutes to about 400 minutes, about 5 minutes to about 360 minutes, and about 30 minutes to about 280 minutes.
[0019] The sonication frequency can range from about 20 kHz to about 100 kHz. For example, the sonication frequency can be at least about 20 kHz, at least about 30 kHz, about 40 kHz, or about 50 kHz. Exemplary ranges include about 20 kHz to about 80 kHz, about 20 kHz to about 60 kHz, and about 50 kHz to about 100 kHz.
[0020] The power delivered by the sonication device can be, for example, in the range of about 50 watts to about 1500 watts. The sonication power can be at least about 100 watts, at least about 250 watts, about 500 watts, or about 1000 watts. Exemplary ranges include about 500 watts to about 1500 watts, about 50 watts to about 1000 watts, and about 250 watts to about 1500 watts.
[0021] Nanodiamond surface functionalization In the processes described herein, it may be desirable to use purified, generally contaminant-free nanodiamonds.Furthermore, it may be desirable to utilize nanodiamonds that include hydrophilic surface groups, particularly nanodiamonds that include surface carboxyl groups and acid anhydrides.
[0022] In some embodiments, the nanodiamond comprises at least about 0.5 mmol of carboxyl groups per gram of nanodiamond, for example, at least about 0.1 mmol of carboxyl groups per gram of nanodiamond, at least about 0.5 mmol of carboxyl groups per gram of nanodiamond, at least about 1 mmol of carboxyl groups per gram of nanodiamond, or at least about 2 mmol of carboxyl groups per gram of nanodiamond. For example, the nanodiamond may comprise from about 0.1 mmol to about 10 mmol of carboxyl groups per gram of nanodiamond, from about 0.5 mmol to about 5 mmol of carboxyl groups per gram of nanodiamond, or from about 1 mmol to about 3 mmol of carboxyl groups per gram of nanodiamond.
[0023] Without wishing to be bound by any particular theory, it is believed that the process described herein is more efficient when applied to hydrophilic nanodiamonds that have a large number of carboxyl groups on their surfaces.
[0024] Thus, the method described herein may include an ozone / oxygen gas mixture oxidation step in which nanodiamond aggregates are purified prior to the disaggregation step. Ozone is a catalyzed by sp 2 Ozone is a powerful oxidizing agent that reacts selectively with carbon. Ozone oxidation of DND results in a high content of oxygen-containing surface groups. In contrast to air oxidation, ozone oxidation proceeds at significantly lower temperatures of 150-200 °C, so that combustion of diamond carbon is minimized. Ozone oxidation is carried out by heating the nanodiamond sample at a temperature of about 100-250 °C, e.g., 150-200 °C, for a period of at least about 72 hours. A suitable mixture contains 0.1 ppm ozone in oxygen gas.
[0025] Without being bound by any particular theory, it is believed that electrostatic repulsion provided by anionic surface groups (e.g., carboxyl groups) may aid in the disaggregation process and prevent re-aggregation of nanodiamond particles. Surface carboxylate groups may dissociate to a greater extent than surface carboxyl groups, thus providing further enhancement of the disaggregation process.
[0026] In various embodiments, the methods described herein may further comprise graphitizing the aggregated nanodiamond aggregates to remove surface functional groups and homogenize surface chemistry. In some embodiments, the methods may further comprise graphitizing the aggregated nanodiamond aggregates and, after graphitization, oxidizing the aggregated nanodiamond aggregates in the presence of ozone at a temperature of about 100°C to about 250°C, or about 150°C to about 200°C. In some embodiments, graphitizing is performed under an inert atmosphere (e.g., a noble gas such as argon) and at a temperature of at least about 900°C, or about 900°C to 1000°C (e.g., 950°C).
[0027] pH In a preferred embodiment, the pH of the slurry is adjusted to at least about 8, for example, from about 8 to about 11. In one preferred embodiment, the slurry pH is adjusted to about 9 to about 10, for example, from 9.2 to 9.8. The pH adjuster can be, for example, 9.5. In one example, the pH adjuster is a 1 M ammonium hydroxide solution.
[0028] Ingredient ratio The concentration of nanodiamonds in the liquid medium must also be high enough to allow efficient dispersion. For example, nanodiamonds may be present in an amount of at least 10 grams per liter of liquid medium, such as at least about 20 g / L, at least about 30 g / L, at least about 40 g / L, or at least about 50 g / L.
[0029] Particle size reduction The methods described herein can be used to produce nanodiamond particles having a median particle size of less than about 50 nm, less than about 40 nm, less than about 30 nm, less than about 25 nm, less than about 20 nm, or less than about 15 nm. The nanodiamond particles have a median effective particle size of at least about 2 nm, preferably less than 10 nm, such as less than about 9 nm, less than about 8 nm, less than about 7 nm, less than about 6 nm, or even less than about 5 nm.
[0030] As used herein, the terms "median effective particle size" and "median particle size" mean that 50% of the nanodiamond particles have a particle size less than the specified value. Using the methods described herein, nanodiamond particles can be produced in which more than 50% of the particles have a particle size below one of the values listed above. For example, at least about 60%, at least about 70%, at least about 80%, at least about 90%, at least about 95%, at least about 98% or at least about 99% of the nanodiamond particles can have a particle size below one of the values listed above.
[0031] The viscosity coefficient of nanodiamond colloids can be measured by conventional methods known to those skilled in the art. For example, the viscosity coefficient of a slurry of discrete nanodiamonds (post-sonication slurry) prepared using the methods described herein can range from at least about 0.8 mPa·s to 5 mPa·s at a temperature of about 25°C.
[0032] By way of non-limiting example, in one series of embodiments, the methods described herein can be used to produce nanodiamond particles in which at least about 60%, at least about 70%, at least about 80%, at least about 90%, at least about 95%, at least about 98% or at least about 99% of the nanodiamond particles have a size less than about 20 nm, such as between 2 nm and about 20 nm. In another series of embodiments, the methods described herein can be used to produce nanodiamond particles in which at least about 60%, at least about 70%, at least about 80%, at least about 90%, at least about 95%, at least about 98% or at least about 99% of the nanodiamond particles have a size less than about 10 nm, such as between 2 nm and about 10 nm.
[0033] The size of nanodiamond particles in a given sample can be measured by conventional particle size measurement techniques known to those skilled in the art. Non-limiting examples of suitable particle size measurement techniques include sedimentation field flow fractionation, photon correlation spectroscopy, disk centrifugation, and static and dynamic light scattering.
[0034] Nanodiamond particles and compositions In another aspect, the present invention relates to nanodiamond particles prepared using the method described herein. Still another aspect relates to compositions comprising said nanodiamond particles. Non-limiting examples of compositions within the scope of the present invention include dry powders, aqueous dispersions and colloidal dispersions comprising said nanodiamond particles.
[0035] For example, pharmaceutical compositions comprising nanodiamond particles prepared using the methods described herein are within the scope of the present invention.
[0036] The nanodiamonds may be characterized by a median particle size that falls within the above ranges. Similarly, the composition may be characterized as including nanodiamonds having a median particle size that falls within the above ranges.
[0037] The aqueous dispersion of nanodiamonds prepared according to the method described herein can be substantially free of aggregates having a particle size of greater than about 250 nm, greater than about 200, greater than about 100 nm, greater than about 90 nm, greater than about 70 nm, greater than about 60 nm or greater than about 50 nm.As used herein, the term "substantially free of aggregates" means that the dispersion contains less than 10% by volume, for example less than 5% by volume, less than 2% by volume, or even less than 1% by volume of the above aggregates relative to the total solid volume of nanodiamonds present in the dispersion.
[0038] The aqueous dispersion of nanodiamonds prepared according to the method described herein may further be characterized by beneficial storage stability.For example, the aqueous dispersion may not show any appreciable precipitation of nanodiamond phase when stored under ambient conditions for at least about 1 day, at least about 1 week, at least about 1 month, or at least about 4 months.
[0039] The dry nanoparticle composition prepared according to the method described herein is also included in the scope of the present invention. Advantageously, the dry nanodiamonds dispersed as described herein can be easily redispersed in water to form an aqueous dispersion with only slightly larger average particle size (e.g., average particle size of less than about 50 nm, less than about 40 nm, less than about 30 nm, less than about 20 nm, less than about 10 nm or less than about 5 nm). This characteristic of the dry nanodiamond composition is significantly more advantageous than nanodiamonds prepared using conventional dispersion techniques, where drying and subsequent redispersion results in the formation of aggregates with average particle size of 1 μm or more.
[0040] Although the body of this disclosure focuses on aggregated and dispersed nanodiamonds, it should be understood that the same principles and considerations can be applied to disperse other hard materials.
[0041] Having described the invention in detail, it will be apparent that modifications and variations are possible without departing from the scope of the invention as defined in the appended claims. EXAMPLES
[0042] The following non-limiting examples are provided to further illustrate the present invention, in which we analyze the quantitative difference between ozone-oxidized DND and standard high-temperature gas-phase-oxidized DND in the presence of oxygen using X-ray photoelectron spectroscopy (XPS) and acid-base potentiometric back titration. In addition, we employ horn sonication in alkaline water to investigate the possibility of deagglomeration of ozone-treated DND without grinding.
[0043] 3. Experimental Procedure 3.1 Sample All DND powders used in this study were manufactured by Daicel Corporation (Osaka, Japan). To produce DND, a 50:50 TNT:RDX charge was detonated under CO2 atmosphere, and the detonation soot was purified in a 1:6 volumetric combination of 70 wt% nitric acid and concentrated sulfuric acid at 150°C for 5 hours. This was followed by multiple cycles of DI water washing and spray drying. Hereafter, we term this material as "as-received DND". As-received DND was oxidized in oxygen and hydrogen gas flow (4% oxygen and 96% nitrogen by volume) at 400°C for 3 hours at Daicel using a tube furnace (KTF045N1, Koyo Thermo Systems Co., Ltd). The resulting material is termed DND-O2.
[0044] 3.2 Oxidation of DND by ozone Prior to ozone oxidation, as-received DND was graphitized in argon flow at 950°C for 5 h using a tube furnace (GSL-1800X, MTI CORPORATION) to remove surface functional groups and homogenize its surface chemistry. This graphitized DND powder (0.5 g) was placed in a 250 ml round-bottom glass flask that was heated to 200°C using an electric mantle heater (HM0250VF1 HEAT MANTLES, BRISKHEAT) with continuous flow of moist ozone / oxygen mixture for 72 h. The mixture was generated by an ozone generator (Ozone Generator B1065, RDEXPAM) and flowed into the reactor through an Erlenmeyer flask filled with 500 ml DI water to provide sufficient humidity in the reactor for HO-assisted ozonolysis. The sample prepared according to this protocol was named DND-O3.
[0045] 3.3 Sonication-assisted hydrolysis 0.6 g of DND-O3 and DND-O2 were mixed separately with DI water to obtain 6.0 wt% slurries. The pH of the slurries was adjusted to 9.5 with 1 M ammonium hydroxide solution. The slurries were sonicated for 280 min using a Fisher Scientific Model 705 Sonic Dismembrator at 50% output power (Figure 1). To follow the progress of dispersal during the course of sonication, 20 μl aliquots of the slurries were taken at regular time intervals and diluted with 6 ml of ammonium hydroxide solution (pH 9.6) and the particle size distribution of DND in the diluted aliquots was measured by DLS. Upon completion of horn sonication, the DND-O3 and DND-O2 slurries were centrifuged at 12000 rpm for 10 min at 25°C using an Eppendorf centrifuge 5810-R and the supernatant from each sample was carefully collected with a pipette (S-DND-O3 and S-DND-O2, respectively). The precipitated portion of DND-O3 was named P-DND-O3 (Figure 1). The precipitated portion from DND-O2 was not collected.
[0046] 3.4 Characterization 3.4.1 Fourier Transform Infrared Spectroscopy (FTIR) FTIR spectra were recorded from 500 to 4000 cm using a Thermo Nicolet NEXUS 470 FT-IR spectrometer. -1 Within 1cm -1 The spectrum of DND was recorded in a potassium bromide pellet made by pressing a mixture of 100 mg KBr and 1 mg DND under a load of 15 tons.
[0047] 3.4.2 X-ray photoelectron spectroscopy (XPS) XPS measurements were performed using a PHI5800 ESCA (ULVAC-PHI Inc.) equipped with a monochromatic AlKa X-ray source. DND samples were adhered to conductive carbon tape. To avoid potential interference from the tape, we ensured that the layer of DND was much thicker compared to the depth of XPS signal collection. The average of O1s and C1s peak areas from two different high-resolution scans was used to calculate the atomic percentage ratio of O to C. The high-resolution scan was performed at a pass energy of 58.7 eV with a step of 0.25 eV.
[0048] 3.4.3 UV-Raman Using HORIBA LabRAM HR Evolution LabSpec 6, the Raman shift range was 900-1900 cm at an excitation wavelength of 325 nm at 0.8 mW. -1 Raman spectra were recorded at 1000 nm. Spectra were averaged over a 20 × 20 μm area with 36 mapping points. Each spectrum was accumulated twice with 4 s exposure to minimize sample damage caused by the laser.
[0049] 3.4.4 Specific surface area (SSA) analysis Specific surface area (SSA) was determined using a NOVA surface area analyzer 2000e (Quantachrome Instruments). Prior to the measurement, the DND samples were degassed under vacuum for 2 h at 200 °C. SSA was calculated using the Brunauer-Emmett-Teller (BET) isotherm from nitrogen adsorption at -196 °C.
[0050] 3.4.5 Acid-base potentiometric back titration Acid-base potentiometric back titration was used to quantify the carboxylic acid (COOH) groups on the DND surface. A 0.05 M NaHCO3 solution was prepared to selectively neutralize the COOH groups. Argon gas was bubbled through the solution for 24 hours at room temperature to remove dissolved CO2. Then, 0.1 g of DND sample was stirred with 15 ml of Ar-purged 0.05 M NaHCO3 solution in a sealed 50 ml plastic centrifuge tube (Karter Scientific 208L2) for 24 hours. After reaction of 0.1 g of DND powder with 15 ml of argon-degassed 0.05 M NaHCO3 solution, the supernatant was separated by centrifugation at 12000 rpm for 30 minutes. A 3 ml aliquot was taken from the supernatant and diluted with 25 ml of argon-degassed 0.01 M NaNO3 solution to obtain a volume sufficient to immerse a pH glass electrode. NaNO3 solution was employed here to maintain the same ionic strength during the titration. The supernatant was separated by centrifugation at 12000 rpm for 30 min and titrated in dynamic equivalence point titration mode with 0.1 M (0.1002 N) HC1 using an 888 Titrando (Metrohm AG) equipped with a pH glass electrode LL Unitrode Pt1000 and a 5 ml dosing burette. As a reference, 15 ml of NaHCO3 solution was stirred for 24 h in a 50 ml plastic centrifuge tube without DND and titrated under the same conditions as above. The amount of NaHCO3 reacted with COOH on the DND surface was determined as the difference between the equivalence points of the reference solution and an aliquot of the sample supernatant (Table 1).
[0051] The equivalence point was determined as the peak position of the first derivative of the titration curve in the pH range of 4.0-4.5, and the results of three different measurements were averaged. The COOH content was then calculated as:
number
[0052] The COOH surface density is then:
number
[0053] 3.4.6 Dynamic Light Scattering (DLS) DLS (Zetasizer Nano ZS, Malvern Instruments Ltd) was used to determine the particle size distribution of the DND dispersions using the viscosity of water (0.82 cP) at 25°C. The distribution and median diameter for the volume distribution (Dv50) were calculated from 10 different measurements per sample. In addition to the distribution on a volume basis, the Z-average of the diluted slurry with ammonium hydroxide solution (pH 9.6) was calculated to obtain the particle size distribution of the large agglomerates by fitting the first part of the correlation function to a single exponential decay model. The diluted slurry was bath sonicated for 5 minutes, after which the DLS measurements and the Z-average diameter were calculated from three measurements per sample.
[0054] 4. Results and Discussion 4.1 Functionalization and characterization of DND surfaces To minimize the content of functional groups and create a more uniform surface prior to ozone oxidation, the as-received DNDs were partially graphitized under argon atmosphere at 950 °C for 5 h, resulting in a yield of 82.2 wt%. By XRD, the partially graphitized DNDs still largely retained their diamond structure (Figure 2). The surface chemistry of the as-received and modified DNDs was evaluated by FTIR in Figure 3. The spectrum of the as-received DNDs (spectrum (1) in Figure 3) shows the most prominent OH stretching (3200–3600 cm -1 ) and displacement (1620~1630cm -1 ) vibration, and 1700-1865 cm -1 They reveal a band of oxygen-containing surface groups corresponding to the C=O stretching vibration at 1733 cm. -1 The carbonyl band at 1771 cm disappeared, but the OH band remained (spectrum (2) in Figure 3). Further oxidation of the surface-graphitized DND in ozone / oxygen reintroduced C=O-containing groups to the surface (spectrum (3) in Figure 3), but the OH band at 1771 cm -1 In contrast to DND-O2 (spectrum (4) in Figure 3), which shows a C=O peak at 1812 cm, the C=O peak of DND-O3 is at a higher frequency. -1 Shifts to anhydride group (C=O>1800cm -1) Moreover, the FTIR spectrum of DND-O3 shows a peak at 1626 cm -1 Compared with the OH bending peak at 1812 cm -1 shows a significantly higher intensity of the C=O peak.
[0055] Acid-base potentiometric back titration and XPS measurements were carried out to quantify the content of surface COOH groups in DND. As shown in Table 2, the experimentally determined surface density of COOH in DND-O3 was 0.927 nm, which is almost twice that of DND-O2. -2 The total oxygen content of the samples was measured by XPS. The XPS ratio of O1s / C1s of DND-O3 is 0.146, which is about 40% higher compared to DND-O2. In principle, the O1s / C1s ratio can be influenced by the primary particle size, since oxygen-containing surface groups are attached to the DND surface, whereas carbon atoms are present both on the surface and in the core of the DND particles. However, the BET measurements suggest that the SSA of DND-O3 is almost equal to that of DND-O2, which means that the O1s / C1s ratio represents the difference in the total oxygen content of the DND surface, not the difference in particle size, between these two samples. Thus, the content of oxygen-containing surface functional groups is higher upon ozone oxidation. For comparison, in the literature data for DND oxidized in air at 400 °C for 24 h, titrations show that the SSA of DND-O3 is 0.15-0.80 nm for long-term air oxidation. -2 The COOH content reached 331m 2 / g to 292m 2 / g. At temperatures above 400 °C, air oxidation appears to result in the simultaneous generation of oxygen-containing surface groups and the burn-off of small DNDs. Ozone oxidation is easier to control, as it proceeds at 200 °C and produces a high content of oxygen-containing functionality with minimal DND burn-off. [Table 2]
[0056] 4.2 Dispersion of DND by Horn Sonication The pH of the DND solution is an important factor affecting colloidal stability. a At pHs higher than 9.5, dissociation of COOH is favored, resulting in a negatively charged DND surface. Therefore, we adjusted the pH to 9.5 before horn sonication of DND-O2 and DND-O3 aqueous suspensions. It is well known that excessive disaggregation processes using wet ball milling with zirconia beads or horn sonication can initially lead to aggregate destruction but later re-agglomeration. Re-agglomeration of DNDs during BASD has also been reported. Therefore, measurements were performed to follow the particle size of DNDs during the horn sonication process. Figure 4 shows the Z-average diameter of the diluted DND-O3 slurry during the horn sonication period. The particle size of the larger aggregates of DND-O3 decreased continuously over the first 90 min, but re-agglomeration was observed after 120 min of sonication. However, DLS measurements taken after centrifuging the slurries at 4500 rpm for 5 min to remove larger aggregates show that DND-O3 disaggregated more rapidly during 280 min of horn sonication, with a Z-average diameter of 71 nm, while the disaggregation efficiency of DND-O2 dropped to zero after 280 min with a minimum Z-average diameter of 77 nm (Figure 4b). Since Z-average is more sensitive to larger aggregates, this experiment shows that DND-O3 is more resistant to reaggregation during horn sonication. For these DLS measurements, 20 μl aliquots were diluted with 6 ml of ammonium hydroxide solution (pH 9.6) before measurements were taken. During these measurements, we noticed that the DND-O2 slurry stuck better to the hydrophobic walls of the centrifuge tube, which may suggest a less hydrophilic nature of DND-O2 or an increase in the viscosity of the slurry (Figure 4c).
[0057] After 280 min of horn sonication, ultracentrifugation at 12000 rpm for 10 min was performed on each sample to completely remove large aggregates, resulting in very dark transparent colloids (S-DND-O3 and S-DND-O2). The particle size distribution of S-DND-O3 and S-DND-O2 shows a sharp peak corresponding to a Dv50 of 5.9 and 10.4 nm, respectively (Fig. 4d). Moreover, the Z-average diameter of S-DND-O3 and S-DND-O2 diluted to 0.02 wt% in ammonium hydroxide solution (pH 9.6) was 39.2 nm for S-DND-O3, which is smaller than that of S-DND-O2 (46.5 nm), suggesting that S-DND-O3 is less aggregated than S-DND-O2. The horn sonication process gives a yield of >80% DND in the supernatant relative to the initial DND mass, comparable in this respect to the yield of the more expensive and difficult BASD. Thus, our results suggest that ozone-oxidized DND can be deaggregated into aqueous colloids an order of magnitude better than air-oxidized DND using horn sonication without any grinding media and with ultracentrifugation (Table 3).
[0058] S-DND-O3 and S-DND-O2 were collected and dried using a rotary evaporator. The dried powders (4 mg each) were mixed with 20 ml of DI water (Figure 5). Surprisingly, the dried S-DND-O3 showed complete redispersibility in DI water without any measures, while S-DND-O2 sank and stayed at the bottom. Inspired by this observation, we prepared a thick 6 wt% slurry of S-DND-O3 powder in DI water and adjusted its pH to 9.5 with 1 M ammonium hydroxide solution. After 30 min of low power bath sonication and 30 min of ultracentrifugation of the slurry at 12000 rpm at 25°C, single-digit DND aqueous colloids were recovered with a yield of more than 70% relative to the initial mass of S-DND-O3 (Figure 6 and Table 4). Similar redispersibility from the dry state was observed in SAUD deagglomerated DND from different manufacturers. [Table 3] [Table 4]
[0059] The distribution was determined by DLS using the viscosity of water (0.82 cP) at 25° C. The median diameter for the volume distribution (Dv50) was calculated from 10 different measurements. In addition to the distribution on a volume basis, the Z-average diameter of the diluted slurry (0.02 wt %) with ammonium hydroxide solution (pH 9.6) was obtained from the average of three different measurements.
[0060] 4.3 Characterization of S-DND-O3 S-DND-O3 was further investigated by UV-Raman and FTIR to clarify its structure and surface chemistry. To understand the reason for the improved dispersion stability of S-DND-O3, we analyzed the difference in surface chemistry between DND-O3, S-DND-O3, and P-DND-O3. P-DND-O3 was obtained as a precipitate after ultracentrifugation by a discrete process (Figure 1 (3)). FTIR of S-DND-O3 showed that the ion-exchange peak of DND-O3 (1812 cm) was smaller than that of DND-O3 (1822 cm). -1 ) with a lower frequency C=O peak (1787 cm -1 ), suggesting hydrolysis of the surface anhydride. Judging from the peak positions, P-DND-O3 is hydrolyzed less than S-DND-O3 (Figure 7a). In addition, the SSA (344m) of S-DND-O3 was significantly higher than that of S-DND-O3 (Figure 7b). 2 / g) is DND-O3 (299m 2 / g), both were obtained from the same as-received DNDs. The difference in SSA is related to the difference in particle size as inferred from the UV Raman spectra (Fig. 7b). The UV Raman spectra of DND-O3, S-DND-O3 and P-DND-O3 all show smaller peaks (1250 cm -1 ) and large (1327cm -1 ) from the diamond scattering domain, and the G band of graphitic carbon (1580 cm -1 ), OH angle angle (1640cm -1 ) and C=O stretching (1725cm -1) P-DND-O3 shows a stronger diamond peak at 1327 cm compared to the other samples. -1 , which may be due to a higher content of larger DND particles in the precipitate. Thus, the SSA and UV Raman data suggest a non-uniform primary particle size distribution of the as-received DNDs and confirm that horn sonication of ozone-oxidized DNDs followed by ultracentrifugation facilitates DND fractionation. A possible explanation for this effect could be that the larger primary particles of DNDs have a lower reactivity towards ozone and are therefore less susceptible to deagglomeration by horn sonication.
[0061] 5 Conclusion Ozone-oxidized DND was quantitatively investigated by acid-base potentiometric back titration and XPS, which revealed a large amount of oxygen-containing surface groups compared to air-oxidized DND. Moreover, ozone-oxidized DND has high resistance to re-agglomeration during the horn sonication process, allowing longer sonication times to generate smaller particles (down to single-digit DND dispersions) without any grinding media. The most prominent feature of ozone-treated and deagglomerated DND is its redispersibility in water from dry powder, which is caused by the large number of oxygen-containing surface groups (mainly anhydrides) generated by ozone treatment and further hydrolyzed to COOH during horn sonication. Sonication-assisted hydrolysis of ozone-oxidized DND may be a commercially viable technique to obtain single-digit DND colloids with COOH termination due to better control, milder conditions, and less burnout of the smallest DND particles compared to air oxidation.
[0062] When introducing elements of the invention or embodiment(s) thereof, the articles "a", "an", "the" and "above" are intended to mean that there are one or more of the elements. The terms "comprising", "including" and "having" are intended to mean that there may be additional elements other than the listed elements.
[0063] In view of the above, it will be seen that the several objects of the invention are achieved and other advantageous results attained.
[0064] Various modifications may be made to the compositions and processes described above without departing from the scope of the invention. All matters contained in the above description and shown in the accompanying drawings are intended to be illustrative, but not limiting. It is intended that the terms be construed as illustrative rather than descriptive. The disclosure of this specification may include the following aspects. (Aspect 1) A method for disaggregating nanodiamond aggregates, comprising the steps of: Mixing the aggregated nanodiamond aggregates in a liquid medium containing a solvent with the ozone oxidized nanodiamond aggregates. wherein the aggregates and the solvent are in a slurry having a pH of about 8 to about 11; and sonicating the mixture for a time sufficient to produce nanodiamond particles having a median particle size smaller than the median particle size of the aggregated nanodiamond aggregates. The method comprising: (Aspect 2) The method of embodiment 1, further comprising oxidizing the aggregated nanodiamond aggregates in the presence of ozone at a temperature of about 100°C to about 250°C, or about 150°C to about 200°C. (Aspect 3) The method of embodiment 1 or embodiment 2, wherein the method is carried out in the absence of any grinding media or disintegrating agents. (Aspect 4) The method of any one of aspects 1 to 3, wherein the aggregate and the solvent are in a slurry having a pH of about 9 to about 10. (Aspect 5) 5. The method of any one of the preceding claims, wherein the nanodiamond particles have an average particle size of less than 10 nanometers. (Aspect 6) The method according to any one of the preceding claims, wherein the nanodiamond particles have a median particle size of less than about 50 nm, less than about 40 nm, less than about 30 nm, less than about 25 nm, less than about 20 nm, less than about 15 nm, less than 10 nm, such as less than about 9 nm, less than about 8 nm, less than about 7 nm, less than about 6 nm or less than about 5 nm. (Aspect 7) 7. The method of any one of the preceding claims, wherein the nanodiamond particles have a median particle size of at least about 2 nm. (Aspect 8) The method according to any one of the preceding claims, wherein at least about 60%, at least about 70%, at least about 80%, at least about 90%, at least about 95%, at least about 98% or at least about 99% of the nanodiamond particles have a particle size of less than about 20 nm, or between about 2 nm and about 20 nm. (Aspect 9) The method according to any one of the preceding claims, wherein at least about 60%, at least about 70%, at least about 80%, at least about 90%, at least about 95%, at least about 98% or at least about 99% of the nanodiamond particles have a particle size of less than about 10 nm, or between 2 nm and about 10 nm. (Aspect 10) 10. The method of any one of aspects 1-9, wherein the mixture is sonicated at a sonication frequency of at least about 20 kHz, at least about 30 kHz, about 40 kHz, or about 50 kHz. (Aspect 11) 11. The method of any one of aspects 1 to 10, wherein the mixture is sonicated at a sonication frequency of about 20 kHz to about 100 kHz, about 20 kHz to about 80 kHz, about 20 kHz to about 60 kHz, or about 50 kHz to about 100 kHz. (Aspect 12) 12. The method of any one of aspects 1-11, wherein an ultrasonic treatment power in the range of about 50 Watts to about 1500 Watts, about 500 Watts to about 1500 Watts, about 50 Watts to about 1000 Watts, or about 250 Watts to about 1500 Watts is delivered to the mixture. (Aspect 13) The method of any one of the preceding claims, wherein the nanodiamond particles comprise at least about 0.1 mmol of carboxyl groups per gram of nanodiamond, at least about 0.5 mmol of carboxyl groups per gram of nanodiamond, at least about 1 mmol of carboxyl groups per gram of nanodiamond, or at least about 2 mmol of carboxyl groups per gram of nanodiamond. (Aspect 14) 14. The method of any one of claims 1 to 13, wherein the nanodiamond particles contain from about 0.1 mmol to about 10 mmol of carboxyl groups per gram of nanodiamond, from about 0.5 mmol to about 5 mmol of carboxyl groups per gram of nanodiamond, or from about 1 mmol to about 3 mmol of carboxyl groups per gram of nanodiamond. (Aspect 15) 15. The method of any one of the preceding claims, wherein the nanodiamonds are present in the slurry in an amount of at least 10 grams per liter of the liquid medium, at least about 20 g / L, at least about 30 g / L, at least about 40 g / L, or at least about 50 g / L. (Aspect 16) 16. The method of any one of the preceding aspects, wherein the viscosity of the slurry after the ultrasonic treatment is in the range of at least about 0.8 mPa·s to 5 mPa·s at a temperature of about 25° C. (Aspect 17) The method of any one of aspects 1 to 16, wherein the solvent comprises water. (Aspect 18) The method according to any one of aspects 1 to 17, wherein the aggregated nanodiamond aggregates are graphitized. (Aspect 19) Graphitizing the aggregated nanodiamond aggregates; and After the graphitization, the aggregated nanodiamond aggregates are oxidized in the presence of ozone at a temperature of about 100° C. to about 250° C., or about 150° C. to about 200° C. 19. The method according to any one of aspects 1 to 18, further comprising: (Aspect 20) 20. The method of embodiment 18 or embodiment 19, wherein the graphitizing is carried out under an inert atmosphere and at a temperature of at least about 900° C., or between about 900° C. and 1000° C.
Claims
1. A method for disaggregating nanodiamond aggregates, comprising the steps of: Mixing the aggregated nanodiamond aggregates in a liquid medium containing a solvent with the ozone oxidized nanodiamond aggregates to obtain a mixture. wherein the aggregated nanodiamond aggregates and the solvent are present in a slurry having a pH of about 8 to about 11; and sonicating the mixture for a time sufficient to produce nanodiamond particles having a median particle size smaller than the median particle size of the aggregated nanodiamond aggregates. Including, The method, wherein the nanodiamond particles have a median particle size of less than about 10 nm.
2. The method of claim 1, further comprising oxidizing the aggregated nanodiamond aggregates in the presence of ozone at a temperature of about 100°C to about 250°C, or about 150°C to about 200°C, prior to the ultrasonic treatment.
3. 3. The method of claim 1 or claim 2, wherein the method is carried out in the absence of any grinding media or dispersing agents.
4. 4. The method according to any one of claims 1 to 3, wherein the aggregated nanodiamond aggregates and the solvent are present in a slurry having a pH of about 9 to about 10.
5. The method according to any one of claims 1 to 4, wherein the nanodiamond particles have an average particle size of less than 10 nanometers.
6. 6. The method of any one of claims 1 to 5, wherein the nanodiamond particles have a median particle size of less than about 9 nm, less than about 8 nm, less than about 7 nm, less than about 6 nm, or less than about 5 nm.
7. The method of any one of claims 1 to 6, wherein the nanodiamond particles have a median particle size of at least about 2 nm.
8. The method according to any one of claims 1 to 7, wherein at least about 60%, at least about 70%, at least about 80%, at least about 90%, at least about 95%, at least about 98% or at least about 99% of the nanodiamond particles have a particle size of less than about 10 nm, or between 2 nm and about 10 nm.
9. 9. The method of any one of claims 1 to 8, wherein the mixture is sonicated at a sonication frequency of at least about 20 kHz, at least about 30 kHz, about 40 kHz or about 50 kHz.
10. 10. The method of any one of claims 1 to 9, wherein the mixture is sonicated at a sonication frequency of about 20 kHz to about 100 kHz, about 20 kHz to about 80 kHz, about 20 kHz to about 60 kHz, or about 50 kHz to about 100 kHz.
11. 11. The method of any one of claims 1 to 10, wherein an ultrasonic treatment power in the range of about 50 Watts to about 1500 Watts, about 500 Watts to about 1500 Watts, about 50 Watts to about 1000 Watts, or about 250 Watts to about 1500 Watts is delivered to the mixture.
12. The method of any one of claims 1 to 11, wherein the nanodiamond particles comprise at least about 0.1 mmol of carboxyl groups per gram of nanodiamond, at least about 0.5 mmol of carboxyl groups per gram of nanodiamond, at least about 1 mmol of carboxyl groups per gram of nanodiamond, or at least about 2 mmol of carboxyl groups per gram of nanodiamond.
13. The method according to any one of claims 1 to 12, wherein the nanodiamond particles contain about 0.1 mmol to about 10 mmol of carboxyl groups per gram of nanodiamond, about 0.5 mmol to about 5 mmol of carboxyl groups per gram of nanodiamond, or about 1 mmol to about 3 mmol of carboxyl groups per gram of nanodiamond.
14. 14. The method of any one of claims 1 to 13, wherein the nanodiamonds are present in the slurry in an amount of at least 10 grams per liter of the liquid medium, at least about 20 g / L, at least about 30 g / L, at least about 40 g / L, or at least about 50 g / L.
15. 15. The method of any one of claims 1 to 14, wherein the viscosity of the slurry after the ultrasonic treatment is in the range of at least about 0.8 mPa s to 5 mPa s at a temperature of about 25°C.
16. The method of any one of claims 1 to 15, wherein the solvent comprises water.
17. The method according to any one of claims 1 to 16, wherein the aggregated nanodiamond aggregates are graphitized.
18. Graphitizing the aggregated nanodiamond aggregates; and After the graphitization, oxidizing the aggregated nanodiamond aggregates in the presence of ozone at a temperature of about 100° C. to about 250° C., or about 150° C. to about 200° C. The method of any one of claims 1 to 17, further comprising:
19. 19. The method of claim 17 or claim 18, wherein the graphitizing is carried out under an inert atmosphere and at a temperature of at least about 900°C, or from about 900°C to 1000°C.
Citation Information
Patent Citations
JP1975105590A
Method for refining diamond, and nanodiamond
JP2006273704A
Salt-assisted ultrasonic disaggregation of nanodiamond
JP2018108913A
Nanodiamond material, method and device for purifying and modifying a nanodiamond
US20130121909A1
Method for separating detonation nanodiamonds
US20170355604A1